Circulating Tumor Cells as Predictors of Response and Failure in Breast Cancer Patients Treated with Preoperative Chemotherapy. Issue 1 (January 2013) - Boutrus, Rimoun R.; Raad, Rita F. Abi; Kuter, Irene; Ancukiewicz, Marek; Roberts, Lisa; Solomon, Natalie; Ngo, Taylor; Borick, Heather; Ryan, Paula; Moy, Beverly; Gadd, Michele; Chien, Jo; et al.
Aim: To explore the significance of circulating tumor cells (CTCs) detection in the course of preoperative chemotherapy (PC) and their effect on the outcomes. Methods: Fifty-five patients with stage II/III invasive breast cancer were enrolled into a preoperative clinical trial. Patients were given PC with sequential single-agent doxorubicin and paclitaxel vs paclitaxel followed by doxorubicin. Blood samples (8 mL) were collected from patients before PC, after each phase, and at 6 months intervals during follow-up. Peripheral blood mononuclear cells were isolated and enriched for epithelial cells. Quantitative RT-PCR was used to determine the presence of cytokeratin 19 (CK19) mRNA. Samples were considered positive when the PCR curve crossed the standard threshold curve. Results: After the first phase of chemotherapy, there was a 59% overall reduction in the median tumor volume. The percentage of volume reduction did not differ between patients who presented with detectable CTCs at baseline and those who did not (p=0.89). After the second phase of chemotherapy, there was a further decrease in the median tumor volume to 93% from baseline. There was no correlation between the lack of response and the presence of CTCs either after the first (p=0.36) or second (p=0.5391) phases of PC. The presence of CTCs was a predictor of local or distant relapse (p=0.0411). The detection of CTCs did not affect overall survival (p=0.2569). Conclusion: CTCs can be used as predictors of relapse after definitive treatment of locally advanced breast cancer; however, CTCs detection in peripheral blood during the course of PC does not implicate a particular pattern of response to treatment.